Reducing noise nuisance in open-plan office rooms by masking unwanted sounds with pyramid-shaped sound columns - Witold Mikulski (Nofer Institute of Occupational Medicine, 2022)
Background In order to obtain appropriate, acoustic conditions of working environment in open plan offices, it is necessary to apply quite a large acoustic treatment in these rooms (e.g., to achieve reverberation time 0.2-0.4 s). However, in cases where the background noise levels in rooms are very low (A-weighted sound pressure level <30 dB), then acoustic treatment alone may be insufficient. In such cases, it may be necessary to use a sound system that generate an "artificial" background noise (sound masking system). It is important that the sound masking system must mask the sound in many workplaces. Therefore, sound masking systems contain a large number of sound sources (loudspeakers), evenly distributed throughout the room. Most often, these loudspeakers are placed in a sound-absorbing suspended ceiling. Material and Methods The article considers the possibility of reducing the number of sound masking sources by using 4-loudspeakers columns. These columns use speakers with much smaller dimensions and less power. The shape of the columns and the arrangement of the loudspeakers in the columns result in a directional radiation pattern that allows for a more even distribution of the masking sound in a room. The article provides the criterion of obtaining a uniform masking sound in the open plan offices. These criteria relate to obtaining appropriate masking sound parameters in the working area, and are based on the criterion value of the distraction distance of the room. Results The article provides the results of measurement tests of the uniformity of masking sound in the room with the use of the above-mentioned sound masking columns. Conclusions It is possible to limit the number of standard masking sound sources in the rooms under consideration using pyramid-shaped sound columns with 4 loudspeakers are used. Med Pr. 2022;73(3):229-40